A Novel Method to Treat Obstructive Eustachian Tube Dysfunction in the Mucosal Type of Chronic Otitis Media - Bhat, Vikram Kemmannu; Kawaldar, Shailashree Bheemaraya; Desai, Suhas Suresh (Annals of Otology and Neurotology, 2022)
Introduction  Treatment of Eustachian tube dysfunction has remained an enigma for a long time. Balloon tuboplasty, even though effective, is not considered by many, as it is invasive, expensive, and cumbersome. Hence, we tried to find some simple and inexpensive solution for the same in chronic otitis media. In this background, we evaluated the use of the Eustachian barotubometer to treat obstructive Eustachian tube dysfunction in mucosal chronic otitis media.Materials and Methods  The pilot study was undertaken in a tertiary referral hospital with 25 cases and 30 controls. Case group patients were administered Eustachian barotubometer therapy along with ciprofloxacin-dexamethasone ear drops and xylometazoline nasal drops until the recovery or up to 10 days. Control group patients received the same ear and nasal drops along with Valsalva maneuver for the same duration.Results  The recovery of the Eustachian tube was categorized as complete, partial, or nil. It was found that the case group had 60 and 32% complete and partial recovery, respectively, while it was 33.33 and 13.33% in the control group. The recovery was faster with Eustachian barotubometer therapy than with the Valsalva maneuver. No complications were observed with the new procedure.Conclusion  The Eustachian barotubometer is a simple, inexpensive device that can be used to treat Eustachian tube dysfunction in chronic otitis media. This device is particularly suitable for the peripheral health care centers of developing countries.
Keywords: eustachian tube; valsalva maneuver; otitis media